PENDIDIKAN MASYARAKAT MENGENAI PENTINGNYA LINGKUNGAN BERSIH DAN SEHAT DI DESA PATALAN - Wahyuni, Siti; Maulidiyah, Nur Laila; Mala, Pingki Hidayatul; Wardatun, Putri Alfia; Prasetiya, Benny (LPPM STAI Muhammadiyah Probolinggo, 2024)
Caring for the environment is an effort to prevent damage to the natural environment. Environmental care is a personal initiative to preserve it without waiting for an environmental health program to be implemented by an organization. Clean and Healthy Living Behavior (CHLB) is an effort to create a condition by opening communication channels, providing information, and education to help the community in Patalan Village address and improve health issues on their own. Adopting clean and healthy living behaviors can reduce health problems that often occur in the Patalan Village community. The research method used in this study is descriptive research with a qualitative approach, aiming to identify the importance of maintaining environmental cleanliness in the community. The researcher's efforts include individual visits to religious figures in Patalan Village, discussing how religion responds to a dirty and unhealthy environment. Keeping the environment clean requires not only the efforts of assigned personnel but also the awareness of the community and good cooperation in preserving a clean environment. Similarly, maintaining a healthy life, especially the Village Head, should pay more attention to the residents, and community awareness is also essential.